An attempt to improve indoor environment by installing humidity-sensitive air inlets in a naturally ventilated kindergarten building. (January 2017) - Mijakowski, Maciej; Sowa, Jerzy
Abstract: Proper values of hydro-thermal parameters and good air quality indoors are known to have a great influence on human comfort, health and performance, and children are particularly susceptible to poor indoor air quality. On the other hand, there is a tendency in developed countries to modernise educational buildings to reduce energy use, and as a result, outdoor air frequently can no longer penetrate into the buildings through thermally insulated exterior walls or through airtight window frames. This may lead to high concentrations of pollutants generated indoors, increased levels of relative humidity and, often, to overheating. Installation of extra air vents (trickle vents) is sometimes recommended as a solution. The present study focuses on a comparison of passive stack ventilation performance as well as indoor conditions before and after installation of humidity-sensitive air inlets in a kindergarten building. The comparison was based on two one-month-long series of monitoring of temperature, humidity and CO2 concentration which took place before and after the installation. The results were assessed against current recommendations, and the effectiveness of the improvement was discussed. Unfortunately, the analysis of indoor conditions and ventilation performance showed that although humidity-sensitive air inlets improved performance of passive stack ventilation, the effect was not sufficient to meet current Polish and European standards and recommendations for indoor environment in newly designed kindergarten buildings. Highlights: Indoor conditions in kindergarten was poor (CO2 concentration exceeded 4500 ppm, humidity exceeded 70%RH). There were 18 humidity controlled air inlets installed in kindergarten. Measurements of CO2 concentration, indoor temperature and humidity were performed before and after installation of air inlets. Results were showed and discussed. Indoor conditions was improved but still was not accepted (CO2 concentration exceeded 3500 ppm, humidity exceeded 60%RH).